İSLAM HUKUKUNDA KEFFARET CEZALARI - ARSLAN, MÜMİNE (Fırat Üniveristesi, 2011)
Ceza, Yüce Allah'ın, mükellef insanlara, emre muhalefetin karşılığı olarak vermiş olduğu bir yükümlülüktür. Keffaret cezaları da bu yükümlülüklerden biridir. Ancak keffaretlerin diğer cezalardan farklı bir yanı bulunmaktadır; nitekim ceza olmak üzere konmuş olsa da keffaretler, ifa edilişi bakımından bir ibadettir. İbadet ve ceza boyutu olan bu yükümlülük, araştırma konumuzu teşkil etmekte ve tezimizde her iki yönüyle incelenmektedir. Konuyu ağırlıklı olarak İslam ceza hukuku bakımından incelediğimizden, keffaretlerin daha ziyade ceza boyutu üzerinde durulmuştur.Kur'an ve Sünnette dayanakları bulunan keffaret cezalarının, genel olarak altı çeşidi vardır. Bu çalışmada kefaret cezaları daha ziyade Hanefi içtihatları ışığında incelenmiştir.Anahtar Kelimeler: Keffaret, suç, ceza, mükellef.

The Law fine, is an obligation which is beeng opposite of something which comes to people by God?s order. The act of atonement as laid down in Islamic law is one of these punishments. But there are the penance punisment is different from the other ones. Even if they have been punishment, the penance punishment is a kind of worship. There are both of the the Law fine is a obligation the worship and punishment, this responsibility which is bothe a pray and punishment; it has been studied ın our thesis ın dimensions. And exemined by two direction. When we studied the object in view of Islamic Law, we stressed punishment dimentions of penance.There are six kinds of this punishments. İn this study we mainly studied the penance punishment according to the rools and opinions of Hanefi sect.Key Words: Penance, crime (sin / fault), Law fine, obliged to worship
The penance punihments in Islamic Law
Keywords: Din